Socio-economic development of municipalities within urban agglomerations - N. N. Musinova (Вестник университета)
The author studies the problems of socio-economic development of municipalities included in the conditional boundaries of urban agglomerations. When developing the foundations of the state policy of the Russian Federation for the development of local self-government, these issues come to the fore. Their solution is the key to the successful achievement of the goals of national projects and strategic objectives of the spatial development of Russia. The article considers models of management of urban agglomerations, generalizes regional experience on the use of mechanisms of socio-economic development of municipalities within agglomerations, identifies tools that contribute to the integrated development of agglomerations and obstacles that prevent it, substantiates the need to improve federal regulation of the formation and development of agglomerations, preferably in the form of a federal law.